From Worlds to Words and the Other Way Around: the Victorian Inheritance in the - Jukić-Gregurić, Tatjana (2000)

(untitled) (Array)
ohn Fowles's The French Lieutenant's Woman is the first English postmodernist novel to address openly the issue of its Victorian heritage. It offers a new perspective of the issues commonly associated with various postmodernist historicisms. My aim is to analyze the interaction between Fowles's portrayal of the Victorian culture and the Victorians as seen by other British postmodernist writers (Rhys, Barnes, Ackroyd, Byatt, Tennant, Colegate).